Effect of rare-earth doping on the free-volume structure of Ga-modified Te20As30Se50 glass. Issue 27 (26th February 2016) - Shpotyuk, Ya.; Ingram, A.; Shpotyuk, O.; Boussard-Pledel, C.; Nazabal, V.; Bureau, B.
Abstract : Doping with 500 ppmw of Pr 3+ ions is found to depress positron trapping in Te20 As29 Ga1 Se50 glass, this effect being explained in terms of competitive contribution of different occupancy positions available for rare-earth ions and trapped positrons. Abstract : By exploring the positron–electron annihilation technique in positron lifetime measuring mode, it is shown that principal rare-earth (RE) induced structural reconfiguration in Ga-codoped TAS-235 glass (that is a glassy Te20 As29 Ga1 Se50 alloy) is related to occupation of intrinsic free-volume voids by embedded RE ions tightly connected with Ga-based tetrahedrons via strong covalent RE-Se/Te–Ga links. A gradual decrease in the intensity of the second component of two-term decomposed lifetime spectra of annihilating positrons accompanied with a detectable increase in the defect-related positron lifetime (thus inducing essentially a depressed rate in positron trapping) is evidenced by the example of Pr 3+ ions added homogeneously to Te20 As29 Ga1 Se50 glass in the amount of 500 ppmw. Observed changes in positron lifetime spectra are explained in terms of the competitive contribution of different occupancy positions in Ga-codoped glass available for RE ions and trapped positrons.